How is the education component of pulmonary rehabilitation delivered in practice––Is it patient‐centred?. (5th May 2021) - Roberts, Nicola J.; Kidd, Lisa; Kirkwood, Kim; Cross, Jane; Partridge, Martyn R.
Abstract: Objectives: Pulmonary rehabilitation (PR) involves a significant component of education, but little has been published on what educational content is covered or how it is delivered. This survey study set out to investigate how PR education is delivered in practice. Methods: A survey was designed to investigate the current educational delivery and which topics respondents reported should be included in a PR programme. The survey was sent to 11 Scottish PR Action group regional leads. Results: Nine completed the questionnaire (81.8%). Education was reported to be predominately group‐based and face‐to‐face (n = 9, 100%) consisting of between 6 and 12 sessions. Most educational topics lasted 15 min or less, some topic areas were not consistently covered. The educational content was variable and not personalised to individual needs. Three health areas undertook informal literacy assessment at baseline assessment and when tailoring COPD plans. Often attendance at educational sessions was not needed to 'complete' PR. Conclusions: Content and delivery of educational topics were varied, and no consistent outcome measure to assess the effectiveness of education was used. Practice implications: Education needs to be delivered in a patient‐centred way tailoring for literacy skills using a range of different teaching approaches and aids.